Brand Image Pemkab Simalungun dalam Merekonstruksi Objek Wisata Umbul Mabar - Aninda, Putri Sari; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Tourism development relies heavily on brand reputation. In branding tourism, it is important to emphasize branding elements, such as logos, slogans, or the general identity of the tourist location. This can influence the way tourists view tourist attractions. Umbul Mabar shapes its tourism image apart from through brand identity or emphasizes its brand identity by using brand benefit and competence elements, namely showing the benefits and superiority values of tourism. In forming a brand image, Umbul Mabar introduces its tourism through direct communication by holding various events at the tourist location. This research uses brand image theory according to Kotler and Keller. This theory includes dimensions and indicators of brand image. The aim of this research is to understand brand image through the stage of collecting descriptive data or depictions of research subjects, both verbally and in writing.